Aykırılaşma Terimi, Tanımı ve Örneklerinin Tasnifi Üzerine - Özçelik, Sadettin (Kitabevi, 2002)
Turkish examples of dissimilation were pointed out in this article. Known examples are analysed by using the consepts and explanations that are used about dissimilation.
On the Dissimilation Concept and Classification of Its Examples
Keywords: The Examples and Analysis of Dissimilation Concept